2015
DOI: 10.1021/pr500920q
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Serum Bile Acids in a Healthy Chinese Population Using UPLC–MS/MS

Abstract: Bile acids (BAs) are a group of important physiological agents for cholesterol metabolism, intestinal nutrient absorption, and biliary secretion of lipids, toxic metabolites, and xenobiotics. Extensive research in the last two decades has unveiled new functions of BAs as signaling molecules and metabolic regulators that modulate hepatic lipid, glucose, and energy homeostasis through the activation of nuclear receptors and G-protein-coupled receptor signaling in gut-liver metabolic axis involving host-gut micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
107
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 141 publications
(125 citation statements)
references
References 36 publications
14
107
4
Order By: Relevance
“…We found large variations in fasting BA concentrations both within and between individuals, as depicted in Figure 1. This is in line with studies of non-bariatric subjects, which found large diurnal variations within individuals [41,42] and large variations in production and concentrations between individuals [43,44].…”
Section: Discussionsupporting
confidence: 91%
“…We found large variations in fasting BA concentrations both within and between individuals, as depicted in Figure 1. This is in line with studies of non-bariatric subjects, which found large diurnal variations within individuals [41,42] and large variations in production and concentrations between individuals [43,44].…”
Section: Discussionsupporting
confidence: 91%
“…A total of 26 BAs analysis was performed using an established method modified for application to human serum (16). Briefly, an internal standard solution containing 0.1 M d4-CA, d4-UDCA and d4-LCA (C/D/N Isotopes, Quebec, Canada) was added to serum or standard solution includes 26 BAs.…”
Section: Quantitative Analysis Of Bas In Human Serummentioning
confidence: 99%
“…[15][16][17] Within the past decade, LC-MS has been heavily utilized for the separation and detection of BAs in human and animal model biofluid samples. 9,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] The most comprehensive of these methods have a relatively long analytical cycle (> 30 minutes), precluding rapid sample analysis. 21,25,28,30,34 On the other hand, the most rapid methods (< 10 minutes) have limited BA coverage.…”
mentioning
confidence: 99%
“…19,33 The majority of separations have analytical times greater than 20 minutes and intermediate level of BA species coverage (ranging from 11 to 32 species monitored). 9,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Very few LC-MS methods report coverage of tertiary BAs such as sulfate conjugates which have recently been implicated in the important role of the gut microbiota in human metabolism. 9,32,[34][35][36] The analytical foundation of these methods is reversed-phase separation utilizing a C 18 stationary phase, which is suitable for retention and separation of the diverse range of hydrophobicity present among BAs.…”
mentioning
confidence: 99%